Arthroscopic resection as a rapid recovery treatment for Os acetabuli in soccer players who had undergone hip arthroscopy: a case series with 1-year follow-up - Salvador, Jorge; Seijas, Roberto; Ferré-Aniorte, Alfred; Laiz, Patricia; Barastegui, David; Cugat, Ramón (Archives of orthopaedic and trauma surgery, 2022)
Introduction Os acetabuli (OSA) is defined as a radiopaque structure located around the acetabular rim highly related to Femoroacetabular Impingement (FAI). Its treatment depends on the perspective of post-surgical joint instability. Ossicle resection is recommended if the femoral head is covered enough by the labrum. Previous research has described the results of this technique in general population. The aim of this study is to describe the outcomes and the time and rate of return to play (RTP) after hip arthroscopy and OSA removal in soccer players. Methods This study is a retrospective analysis of a prospective database containing all the consecutive soccer players who had undergone hip arthroscopy between 2018 and 2019. The subjects diagnosed with OSA and a center–edge angle (CEA) > 25 ° were included in the analysis. All the patients were treated with arthroscopic removal of the OSA and femoral osteoplasty. Hip function was assessed using the Modified Harris Hip Score (MHHS) before and at 3 and 12 months after surgery. Rate of RTP and competitive level at RTP were assessed at a 1-year follow-up. Results Between 2018 and 2019, 90 soccer players were treated with hip arthroscopy in our facilities. Six of them (6.6%) were diagnosed with OSA. Mean (SD) MHHS values were 69.7 (12.1) before the surgery, 89.7 (6.7) at 3 months post-surgery and 95.7 (5.1) at 12 months post-surgery. All the subjects reported significant improvements in their MHHS scores at 3 and 12 months post-surgery compared with pre-surgery levels ( p < 0.01). Non-significant differences were found between 3 and 12 months post-surgery ( p > 0.05). All the subjects (100%) returned to previous competitive levels. Conclusions After surgery, all the soccer players returned to previous competitive level. Preoperative MHHS improved significantly at 3 months maintained for up to 12 months.